Effects of supplemental fulvic acid on survival, growth performance, digestive ability and immunity of large yellow croaker (Larimichthys crocea) larvae - Zhang, Chenxiang; Liu, Yongtao; Yao, Chuanwei; Zhang, Jianmin; Wang, Yuntao; Liu, Jiahui; Hong, Yucong; Mai, Kangsen; Ai, Qinghui (Frontiers in Physiology, 2023)
A 30-day feeding trial was designed to evaluate the effect of supplemental fulvic acid (FA) on survival, growth performance, digestive ability and immunity of large yellow croaker (Larimichthys crocea) larvae (initial body weight 11.33±0.57 mg). Four isonitrogenous and isolipids diets containing 0.00%, 0.01%, 0.02% and 0.04% FA were formulated, respectively. Results showed that the supplementation of 0.04% FA significantly improved survival rate of large yellow croaker larvae. Supplemental FA significantly increased final body weight and specific growth rate. Based on the specific growth rate, the optimal supplementation was 0.0135% FA. Larvae fed the diet with 0.01% FA had significantly higher villus height than the control. The supplementation of 0.01%-0.02% FA significantly increased the muscular thickness of intestine. Moreover, compared with the control, supplementation of FA remarkably increased activities of alkaline phosphatase and leucine aminopeptidase in the brush border membrane of intestine. Diets supplemented with 0.02%-0.04% FA significantly increased the activity of trypsin in the intestinal segment, while 0.01%-0.02% FA significantly increased the activity of trypsin in the pancreatic segment. Meanwhile, supplementation of FA significantly increased mRNA expression of intestinal epithelial proliferation and barrier genes (pcna, zo-1 and zo-2). Furthermore, larvae fed the diet with 0.01% FA significantly increased activities of lysozyme and total nitric oxide synthase. The supplementation of 0.01% to 0.02% FA significantly decreased the mRNA expression of pro-inflammatory cytokines tnf-α and il-6. Concurrently, supplemental FA significantly increased anti-inflammatory cytokine il-10 mRNA expression level. In conclusion, this study indicated that the supplementation of FA could improve the survival rate and growth performance of larvae by promoting intestinal development, digestive enzymes activities and innate immunity.